AESTHETIC DISENSUS: JAVANESE ISLAMIC AESTHETICS AND POLITICAL SUBVERSION IN BABAD TANAH JAWI - Fawaid, Achmad; Faridy; Moh. Fachri; Ridhatullah Assy’abani; Miftahul Huda (UIN Antasari Banjarmasin, 2024)
This study uses the framework of aesthetic politics to analyze Javanese Islam as depicted in Babad Tanah Jawi, challenging colonial misconceptions about Javanese Islam while offering new perspectives on religious and cultural dynamics in Java. By critiquing colonial myths, this study highlights the unique heterogeneity of Javanese Islam in its various everyday practices, contrasting Western essentializations with the local particularities depicted in the manuscript. Based on Rancière's concept of aesthetic politics, this research employs critical discourse analysis to explore how Javanese Islam is not only theoretical but also practical and performative, critiquing Western views that overlook the dynamic nature of Islam itself. Emphasizing disensus and disagreement within Javanese Islamic traditions, this analysis rejects the essentialization of Islam, presenting it as a flexible practice that defies easy categorization into a single identity. This study also underscores how Javanese Islamic practices challenge Orientalist interpretations by integrating local Javanese perspectives on one hand and rejecting Western essentialist classifications on the other. The implication of this research is the need to reevaluate Javanese Islam through various literary texts, not to render it as unreliable text, but rather to place it as the subjective aesthetic choice of the author in questioning the colonial narratives that have long prevailed in the historiography of Javanese Islam.